Trans-obturator cystocele repair of level 2 paravaginal defect - Kalis, Vladimir; Kovarova, Veronika; Rusavy, Zdenek; Ismail, Khaled M (International urogynecology journal, 2020)
INTRODUCTION AND HYPOTHESIS: It is reported that almost one in five women will need some form of pelvic organ prolapse surgery in their lifetime, with anterior wall repair accounting for nearly half of these. Cystoceles occur secondary to defect(s) in one or more of the vaginal wall support mechanisms, including its lateral paravaginal attachments. Paravaginal defects are very common in women presenting with cystocele, thus highlighting the importance of paravaginal defect repair for optimal cystocele correction in the majority of cases. Although there are several paravaginal defect repair procedures, some entail complex techniques, whereas others rely on the use of transvaginal mesh, which is currently not permitted in many countries. METHODS: In this video article we present a novel trans-obturator native tissue paravaginal defect repair for the management of cystocele. RESULTS: This procedure has the advantages of avoiding complex transabdominal paravaginal defect repair, the controversial use of transvaginal mesh, or a single-point fixation to an arcus tendineus fasciae pelvis that might be difficult to identify. CONCLUSION: We believe that the trans-obturator cystocele repair procedure offers several advantages over existing paravaginal defect repair alternatives.
Keywords: prolaps pánevních orgánů; Surgical Mesh; chirurgické síťky; Abdomen; Arcus tendineus fasciae pelvis; Pelvic Organ Prolapse; Fascia; Cystocele; Native tissue; lidé; Repair; ženské pohlaví; Humans; Obturator paravaginal; fascie; Female; Vagina; vagina; Transobturator; cystokéla; břicho